Changes in demand for emergency ambulances during a nationwide lockdown that resulted in elimination of COVID-19: an observational study from New Zealand. Issue 12 (23rd December 2020) - Dicker, Bridget; Swain, Andrew; Todd, Verity Frances; Tunnage, Bronwyn; McConachy, Emma; Drake, Haydn; Brett, Michelle; Spearing, Dan; Howie, Graham John
Abstract : Objective: To examine the impact of a 5-week national lockdown on ambulance service demand during the COVID-19 pandemic in New Zealand. Design: A descriptive cross-sectional, observational study. Setting: High-quality data from ambulance electronic clinical records, New Zealand. Participants: Ambulance records were obtained from 588 690 attendances during pre-lockdown (prior to 17 February 2020) and from 36 238 records during the lockdown period (23 March to 26 April 2020). Main outcome measures: Ambulance service utilisation during lockdown was compared with pre-lockdown: (a) descriptive analyses of ambulance events and proportions of event types for each period, (b) absolute rates of ambulance attendance (event types/week) for each period. Results: During lockdown, ambulance patients were more likely to be attended at home and less likely to be aged between 16 and 25 years. There was a significant increase in the proportion of lower acuity patients (Status 3 and Status 4) attended (p<0.001) and a corresponding increase in patients not transported from scene (p<0.001). Road traffic crashes (p<0.001) and alcohol-related incidents (p<0.001) significantly decreased. There was a decrease in the absolute number of weekly ambulance attendances (ratio (95% CI), 0.89 (0.87 to 0.91), p<0.001), attendances to respiratory conditions (0.74 (0.61 to 0.86), p=0.01), and trauma (0.81 (0.77 to 0.85), p<0.001). However, there was a significant increase in ambulance attendances for mental health conditions (1.37 (1.22 to 1.51), p=0.005). Conclusions: Despite the relative absence of COVID-19 in the community during the 5-week nationwide lockdown, there were significant differences in ambulance utilisation during this period. The lockdown was associated with an increase in ambulance attendances for mental health conditions and is of concern. In considering future lockdowns, the potential implications on a population's mental well-being will need to be seriously considered against the benefits of elimination of virus transmission.